A principled Cognitive Linguistics account of English phrasal verbs with up and out*. (16th May 2014) - MAHPEYKAR, NARGES; TYLER, ANDREA
Abstract : Many attempts have been made to discover some systematicity in the semantics of phrasal verbs. However, most research has investigated the semantics of particles exclusively; no study has examined how the multiple meanings of the verb also contribute to the meanings of phrasal verbs. The current corpus-based (COCA) study advances the research on phrasal verbs by examining the interaction of the polysemy networks of both the verb and the particle in four phrasal verb constructions: get up, take up, get out, and take out . Following the Cognitive Linguistics (CL) based methodology set out by Tyler and Evans (2003 ) for analyzing the semantics of particles, in conjunction with Langacker's (1991 ) analysis of the semantics of verbs, a replicable polysemy analysis of the semantics of get and take was established. The polysemy networks for both the verbs and the particles laid the foundation for investigating the multiple meanings of the phrasal verbs found in the corpus. The CL-based analysis of the semantics of the phrasal verb constructions provides evidence for the compositional nature of phrasal verbs, showing that the multiple meanings can be systematically accounted for through the interaction of the polysemy networks of the component verbs and particles.